Chicago Paper - Mud Volcanoes of Colombia, South American - Stanley C. Herold (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
A few hates on the occurrence and significance of mud volcanoes in Colombia may be of interest at the present time, owing to the renewed activity in geological exploration of the coastal regions bordering the Caribbean Sea. The best-known volcanoes are found a few miles from the seacoast. One is situated to the south of Puerto Colombia; the second, to the east of Cartagena near the village of Turbaco; and the third, near the village of Puerto Escondido south of the Sinu River. Others are reported in more inaccessible localities. Usually they stand 2 1/2 or 3 ft. (0.762 or 0.914 m.) above the surrounding ground at the crater, though several craters from 10 to 20 ft. -(3.04 to 6.09 m.) "apart will often build up an extensive mound at low gradient. The shallow mound may cover 1/2 or 3/4 acre (0.2 to 0.3 ha.) with an elevation of 12 or 15 ft. (3.65 or 4.57 m.) at the, center. The craters are formed of hardened blue clay; the inside diameters vary from 14 to 24 in. (35.56 to 60.96 cm.). The rim is continuous, except on one side where there is usually a cut 3 or 4 in. deep, thus allowing an overflow. The craters are filled to the' rim-cut with a thick mixture of blue clay mud and water, which is kept in agitation by escaping gas. Fig. 1 shows the bubble in the act of bursting and Fig. 2 the appearance of the surface of the viscous fluid a second or so later. The frequency of the explosions is determined by the weight of the column of fluid in the neck of the volcano, consequently, such explosions are not synchronous in a group of craters. Ordinarily, there arc two or three explosions in about 3 minutes. The supply of gas is small but steady and sufficient pressure must accumulate before the bubble can enter the column of fluid. The water is derived from the surface and enters the scdirnentary strata not far distant from the volcano. During long dry seasons, as the supply of water fails the volcano dries and geyser action ceases. The temperature of the muddy fluid is normal; the gas is dry and inflammable. - No petroleum products come with the gas. On the surface of the fluid, there is sometimes a dark brown streaky scum, which